2017
DOI: 10.1007/s11266-017-9918-1
|View full text |Cite
|
Sign up to set email alerts
|

Helping Dutch Neighborhood Watch Schemes to Survive the Rainy Season: Studying Mutual Perceptions on Citizens’ and Professionals’ Engagement in the Co-Production of Community Safety

Abstract: Despite the growing research interest in coproduction, some important gaps in our knowledge remain. Current literature is mainly concerned with either the citizens or professionals being involved in co-production, leaving unanswered the question how co-producers and professionals perceive each other's engagement, and how this is reflected in their collaboration. This study aims to answer that question, conducting an exploratory case study on neighborhood watch schemes in a Dutch municipality. Empirical data ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 34 publications
1
18
1
Order By: Relevance
“…Even in member NPOs, the participation experience matters. van Eijk (2018) found that residents in neighborhood watch schemes wanted to be appreciated for their contributions by other members and, more importantly, by professionals (in this case, municipal police officers).…”
Section: Current Research On Nonprofits: Beneficiaries As Organizatiomentioning
confidence: 99%
“…Even in member NPOs, the participation experience matters. van Eijk (2018) found that residents in neighborhood watch schemes wanted to be appreciated for their contributions by other members and, more importantly, by professionals (in this case, municipal police officers).…”
Section: Current Research On Nonprofits: Beneficiaries As Organizatiomentioning
confidence: 99%
“…Such tools should support different stakeholders to provide and get mutually beneficial information. The police officers could balance their workloads by focusing on serious crimes and allowing petty crimes [7] to be handled by other stakeholders. Incentive mechanisms (e.g., rewards) could be provided to encourage citizens to actively participate in crime prevention and activity in their local community.…”
Section: Multi-stakeholder Collaboration Platformmentioning
confidence: 99%
“…Likewise, we argue that organizational support for coproduction provides professionals with a solid resource and cultural and organizational backup when interacting with clients/citizens in autonomy. The support offered by the organization stimulates professionals’ belief that they are trusted by the organization to go outside, to develop new modes of interaction with the outside world, and are allowed to make decisions with and based on citizens’ views (Spiegel, 1987; Van Eijk, 2018). Consequently, organizational support will positively impact on professionals’ engagement in coproduction by enforcing their feeling of work autonomy.…”
Section: Characteristics Of Professionals’ Work Environmentmentioning
confidence: 99%